INDEPENDENT WORK OF STUDENTS OF TECHNICAL UNIVERSITIES AS A WAY TO FORM COMMUNICATIVE COMPETENCE IN ENGLISH LESSONS - Mukhanbetkalieva, G. Sh. (Наука и образование №4, 2020)
At studying any subject, the effectiveness of mastering the material largely depends on properly organized independent work. Consolidation and development of the material studied in the classroom must necessarily be carried out by students independently, taking into account the specifics of a foreign language, its technical orientation and communicative nature. At properly organized independent work, students have the opportunity to develop all types of speech activity - reading, speaking, writing and listening, thus increasing the level of foreign language communicative competence, which is the ultimate goal of teaching a foreign language.
Keywords: научный журнал; отечественное издание; периодическое издание; английский язык; языкознание; иностранный язык; самостоятельная работа студента; independent work; activities; homework; language club; foreign language communicative competence